2016
DOI: 10.33844/ijol.2016.60302
|View full text |Cite
|
Sign up to set email alerts
|

Human resource practices and knowledge sharing: The moderating role of trust

Abstract: Keywords:Human Resource Management, Knowledge Sharing, Performance Appraisals, Compensation, Training. HRM is considered as a backbone for successful organizations and knowledge sharing plays a vital role for an organization to success globally. The purpose of the study is to understand the factors that contribute to knowledge sharing in an organization. This study explains how the effective training, fair compensation and performance appraisal affects the knowledge sharing. The impact of trust on relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Therefore, the presence of trust motivates employees to collaborate and coordinate with one another to positively exchange knowledge. According to Pervaiz et al (2016), when an organization wants to enrich creation, innovation and development of KS, then they should pay attention to HRM practices in a trustworthy environment. Based on the literature review, we propose the following hypotheses to analyze the HRM practices and the trust effect on employee KS behavior.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Therefore, the presence of trust motivates employees to collaborate and coordinate with one another to positively exchange knowledge. According to Pervaiz et al (2016), when an organization wants to enrich creation, innovation and development of KS, then they should pay attention to HRM practices in a trustworthy environment. Based on the literature review, we propose the following hypotheses to analyze the HRM practices and the trust effect on employee KS behavior.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…For instance, Ozlati (2015) found that trust (benevolence-based and institution-based) significantly moderated the relative autonomy-knowledge sharing relationship. Recently, Pervaiz et al . (2016) tested the moderating role of trust on human resource practices and knowledge sharing and found that trust significantly moderated the relationship between human resource practices (such as training, compensation and performance appraisals) and knowledge sharing.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…Knowledge sharing can be improved when people exchange information, best experiences, lessons learned, and insights. Trust in management is one of the main factors influencing employees' decision to share knowledge (Renzl 2008;Pervaiz 2016). Trust is a willingness to be vulnerable (Meyer et al 2017), and it is strongly associated with the belief that other people will not use this situation for their own benefit.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%